(untitled) (The Review of Diabetic Studies, 2025)
This study presents the formulation and evaluation of okra mucilage-based mucoadhesive nanoparticles for the targeted gastrointestinal delivery of metronidazole. Conventional oral metronidazole therapy is limited by rapid systemic absorption, short gastrointestinal residence time, and dose-dependent side effects. To address these challenges, metronidazole-loaded nanoparticles were prepared using the ionic gelation method, employing okra mucilage as a natural polymer. A Quality by Design (QbD) approach with Box-Behnken design was used for optimization, focusing on mucilage concentration, calcium chloride concentration, and stirring speed as formulation variables. The optimized nanoparticles exhibited a mean particle size of 187.4 ± 8.2 nm, polydispersity index of 0.241 ± 0.018, zeta potential of –28.6 ± 2.1 mV, and entrapment efficiency of 78.3 ± 3.4%. Scanning electron microscopy revealed spherical, smooth-surfaced nanoparticles. In vitro studies demonstrated sustained drug release up to 12 hours, while ex vivo tests showed strong mucoadhesive strength and prolonged intestinal retention. Gamma scintigraphy confirmed extended gastrointestinal transit time compared to conventional tablets. Pharmacokinetic analysis indicated lower C_max with comparable bioavailability, reducing peak-related side effects while maintaining therapeutic efficacy. These findings suggest that okra mucilage-based nanoparticles provide a safe, natural, and cost-effective platform for targeted gastrointestinal delivery of metronidazole, improving therapeutic outcomes and patient compliance. However, challenges such as polymer variability and formulation stability require further investigation before clinical translation.